RELIABILITY RESEARCH ROADMAPPING WORKSHOP: IMPLICATIONS FOR ENGINEERING DESIGN. (May 2020) - Campean, F.; Delaux, D.; Sharma, S.; Bridges, J.
Abstract: Transportation industries are the centrepoint for some remarkable transformations driven by technology development and innovation. However, we have seen limited advances on methods to address reliability and resilience challenges emerging with increasingly complex systems and environments. This paper presents the outcomes of an European Reliability Research Roadmapping workshop, collating the views of automotive, aerospace and defence industries to identify current reliability challenges and research gaps and to define directions for future research and skills development.